Designing Game “Belajar Hanacaraka” As A Javanese Script Learning Media - Yonathan Happy Setiawan (SISFORMA, 2017)
This paper discusses the design of games used as a medium of learning. The learning material is about Javanese script, which is taught from elementary to high school. Although it has been taught since elementary school, but not many students have mastered this material.The method of delivering the material used by the lecturers is usually by lecturing so that students become tired and bored, because they are forced to remember without understanding the basic concepts. The lack of an attractive and modern learning tool becomes another obstacle to the difficulty of studying the Javanese script.Games usually used as entertainment, now can be used for learning. Through the game, the learning process becomes more fun. Therefore it will be designed an educational game used for learning Javanese script. But to design the right educational game, research is needed. With the presence of this game is expected players can learn Javanese script material while playing.